2019
DOI: 10.1111/spc3.12447
|View full text |Cite
|
Sign up to set email alerts
|

The narrative identity approach and romantic relationships

Abstract: Narrative identity is an internal and evolving life story in which the narrator integrates conceptions of the personal past, present, and presumed future within a coherent story‐based framework. Carrying a number of personal and social implications, this construct represents a psychological resource. We contend that, like life itself, one's history within the romantic domain as well as one's current romantic relationship(s) are often viewed using story‐based frameworks. As such, we argue that the greater adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 68 publications
(136 reference statements)
0
26
0
Order By: Relevance
“…Previous studies have also shown that other factors affecting long-term marital satisfaction include commitment (Guilbault & Philiphe 2017), sexual desire, longing for each other (Beaudoin et al, 2020), personality traits, the understanding of the relationships in marital life (Bühler & Dunlop 2019), support, love for the partner, embodying a great common goal in life (Gildersleeve 2015), and flexibility in life (Bachand & Carson 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that other factors affecting long-term marital satisfaction include commitment (Guilbault & Philiphe 2017), sexual desire, longing for each other (Beaudoin et al, 2020), personality traits, the understanding of the relationships in marital life (Bühler & Dunlop 2019), support, love for the partner, embodying a great common goal in life (Gildersleeve 2015), and flexibility in life (Bachand & Carson 2001).…”
Section: Discussionmentioning
confidence: 99%
“…That is, compatibility primarily emerges as a consequence of the narrative history and idioms that are created within a particular relationship that does not generalize to other relationships (Bell et al, 1987;Garcia-Rada et al, 2018;Harris et al, 2014;Rossignac-Milon & Higgins, 2018). This perspective generates the prediction that accounting for relationship effects will require that scholars tailor items in a way that incorporates the relationship's own narrative structure (Adler et al, 2017;Bühler & Dunlop, 2019;Sparks et al, 2020). For example, it may be the case that Lawrence feels uniquely positive about Issa because of the way they tease each other-and he would feel less positive if that dynamic changed-but that particular standard would not apply to his past or future relationships.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Narrative identity (namely, the life story; McAdams, 1995) is an internal representation of an individuals' past, present, and presumed future. The narrative identity approach (Bühler & Dunlop, 2019) is predicated on the notion that the manner in which people perceive their pasts takes precedence over what "actually" happened, in any objective sense of the word. With this in mind, these storied representations are understood to be psychosocial constructions insofar as they draw from the important events of one's past, but are changed through reflection, interpretation, and evaluation.…”
Section: Narrative Ways Of Knowingmentioning
confidence: 99%
“…As we articulate below, for many, such sense‐making processes are decidedly story‐like or narrative in nature (Bruner, 1990). As such, a narrative identity approach (Bühler & Dunlop, 2019) stands to inform the phenomenological understanding of romantic infidelity, both from the perspective of victims and perpetrators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation